Using Cargo Bikes in Personal Logistics – Conditions and Possibilities in the Czech Republic - Seidlová, Andrea; Ledvinová, Michaela (Kaunas University of Technology, 2022)
This paper analyses the possibilities to integrate cargo bikes into personal logistics in the Czech Republic. Cargo bikes for personal use are relatively popular in some European countries, such as Netherlands, Denmark, and Germany, also including sharing systems. In the Czech Republic, this kind of use of cargo bike is sporadic. The most common purpose to use cargo bike, is the transport children and shopping. This paper deals with factors, which can influence the level of the use of cargo bikes in various conditions.
Využití nákladních kol v osobní logistice
Keywords: cargo bikes; personal logistic; individual use of cargo bikes; nákladní kola; osobní logistika; individuální použití nákladních kol